Differentiation of COVID-19 signs and symptoms from allergic rhinitis and common cold: An ARIA-EAACI-GA2 LEN consensus - Hagemann, Jan; Onorato, Gabrielle L; Jutel, Marek; Akdis, Cezmi A; Agache, Ioana; Zuberbier, Torsten; Czarlewski, Wienczyslawa; Mullol, Joaquim; Bedbrook, Anna; Bachert, Claus; Bennoor, Kazi S; Bergmann, Karl-Christian; et al. (Allergy, 2021)
BACKGROUND: Although there are many asymptomatic patients, one of the problems of COVID-19 is early recognition of the disease. COVID-19 symptoms are polymorphic and may include upper respiratory symptoms. However, COVID-19 symptoms may be mistaken with the common cold or allergic rhinitis. An ARIA-EAACI study group attempted to differentiate upper respiratory symptoms between the three diseases. METHODS: A modified Delphi process was used. The ARIA members who were seeing COVID-19 patients were asked to fill in a questionnaire on the upper airway symptoms of COVID-19, common cold and allergic rhinitis. RESULTS: Among the 192 ARIA members who were invited to respond to the questionnaire, 89 responded and 87 questionnaires were analysed. The consensus was then reported. A two-way ANOVA revealed significant differences in the symptom intensity between the three diseases (p < .001). CONCLUSIONS: This modified Delphi approach enabled the differentiation of upper respiratory symptoms between COVID-19, the common cold and allergic rhinitis. An electronic algorithm will be devised using the questionnaire.
Keywords: smell; COVID-19; alergická rýma; Consensus; Rhinitis, Allergic; Asthma; cough; Common Cold; allergic rhinitis; lidé; bronchiální astma; Humans; common cold; konsensus; nachlazení; SARS-CoV-2